Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.31234/osf.io/nfzah
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Familiarity impairments after anterior temporal-lobe resection with hippocampal sparing: Lessons learned from case NB

Abstract: We review evidence from an extensive single case study in an individual (NB) who underwent a rare left-sided anterior temporal-lobe resection with sparing of the hippocampus. Our study aimed to determine whether memory functions of perirhinal cortex, which was largely removed in the resection, can be impaired against a background of preserved hippocampus-dependent memory processing. This research was guided by the proposal that item-based familiarity assessment relies on contributions of perirhinal cortex, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This underlines the robustness of the findings and the fact that this result is independent of experimental conditions. Also, as mentioned previously, even though the role of PER in familiarity has been extensively studied in humans and rodents 7 , 12 18 , 39 , evidence for a specific involvement of LEC has been scarce in animals 17 and inexistent in humans. Hence, the extent to which the engagement of LEC and PER during judgments based on familiarity is comparable in healthy subjects or when hippocampal function is compromised was not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This underlines the robustness of the findings and the fact that this result is independent of experimental conditions. Also, as mentioned previously, even though the role of PER in familiarity has been extensively studied in humans and rodents 7 , 12 18 , 39 , evidence for a specific involvement of LEC has been scarce in animals 17 and inexistent in humans. Hence, the extent to which the engagement of LEC and PER during judgments based on familiarity is comparable in healthy subjects or when hippocampal function is compromised was not known.…”
Section: Discussionmentioning
confidence: 99%
“…mainly based on its strong anatomical ties with PER 7 , 8 while others have attributed this function to HIP in addition to its well-established role in the recollection of episodic events 9 11 . Plethora of studies have reported a specific involvement of PER in the familiarity process, especially during spontaneous object recognition memory in rodents and word recognition memory in humans 7 , 8 , 12 18 . In contrast, clear empirical evidence for a selective involvement of LEC in familiarity judgements is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This underlines the robustness of the findings and the fact that this result is independent of experimental conditions. Also, as mentioned previously, even though the role of PER in familiarity has been extensively studied in humans and rodents (Bowles et al, 2007;Bowles et al, 2010;Haskins et al, 2008;Murray, Bussey, & Saksida, 2007;Farovik et al, 2011;Atucha et al, 2017;Köhler and Martin ,2020; see for reviews Brown and Aggleton, 2001;Eichenbaum et al, 2012), evidence for a specific involvement of LEC has been scarce in animals (Atucha et al, 2017) and inexistent in humans. Hence, the extent to which the engagement of LEC and PER during judgments based on familiarity is comparable in healthy subjects or when hippocampal function is compromised was not known.…”
Section: Discussionmentioning
confidence: 99%
“…single objects, odors etc…) mainly based on its strong anatomical ties with PER (Brown and Aggleton et al, 2001; see Eichenbaum et al, 2007 for a review) while others have attributed this function to HIP in addition to its well-established role in the recollection of episodic events (Squire, 1992;Squire and Zola, 1998;Wixted and Squire, 2011). Plethora of studies have reported a specific involvement of PER in the familiarity process, especially during spontaneous object recognition memory in rodents and word recognition memory in humans (Bowles et al, 2007(Bowles et al, , 2010Farovik et al, 2011;Haskins et al 2008;Murray, Bussey, & Saksida, 2007;Atucha et al, 2017;Köhler and Martin, 2020; see for reviews Brown and Aggleton, 2001;Eichenbaum et al, 2007). In contrast, clear empirical evidence for a selective involvement of LEC in familiarity judgements is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it has been postulated to be the nexus of the creation of memories for those individual percepts. This notion is supported by the case of a patient with selective damage to this area, who exhibits specific impairment in feeling familiarity (Köhler & Martin, 2020). In contrast, the hippocampus, a subcortical structure receiving input from the perirhinal cortex, has been identified as a vital locus of memory formation for associations, transitive learning, spatial mapping, and other complex representations (Eichenbaum, 2017).…”
Section: Human Memory Systems and Their Place In The Learning Processmentioning
confidence: 97%